Repetitive levosimendan treatment in the management of advanced heart failure. (2nd November 2018) - Oliva, Fabrizio; Comin-Colet, Josep; Fedele, Francesco; Fruhwald, Friedrich; Gustafsson, Finn; Kivikko, Matti; Borbély, Attila; Pölzl, Gerhard; Tschöpe, Carsten
Abstract: Inotropes may be an appropriate treatment for patients with advanced heart failure (AdHF) who remain highly symptomatic despite optimized standard therapies. Objectives for inotrope use in these situations include relief of symptoms and improvement of quality of life, and reduction in unplanned hospitalizations and the costs associated with such episodes. All of these goals must be attained without compromising survival. Encouraging findings with intermittent cycles of intravenous levosimendan have emerged from a range of exploratory studies and from three larger controlled trials (LevoRep, LION-HEART, and LAICA) which offered some evidence of clinical advantage. In these settings, however, obtaining statistically robust data may prove elusive due to the difficulties of endpoint assessment in a complex medical condition with varying presentation and trajectory. Adoption of a composite clinical endpoint evaluated in a hierarchical manner may offer a workable solution to this problem. Such an instrument can explore the proposition that repetitive administration of levosimendan early in the period after discharge from an acute episode of worsening heart failure may be associated with greater subsequent clinical stability vis-à-vis standard therapy. The use of this methodology to develop a 'stability score' for each patient means that all participants in such a trial contribute to the overall outcome analysis through one or more of the hierarchical endpoints; this has helpful practical implications for the number of patients needed and the length of follow-up required to generate endpoint data. The LeoDOR study (NCT03437226), outlined in this review, has been designed to explore this new approach to outcome assessment in AdHF.